Raising State Minimum Wages, Lowering Community College Enrollment - Schanzenbach, Diane Whitmore; Turner, Julia A.; Turner, Sarah (The Review of Economics and Statistics, 2024)
Abstract Changes in the minimum wage may impact college enrollment and educational attainment. Using institutional data on college enrollment and program completion, we find that enrollment falls markedly among students at public two-year institutions in response to increases in the minimum wage. The largest enrollment effects are seen for those students who are enrolled part-time at community colleges. We find little evidence of negative effects on the attainment of certificates or degrees, suggesting that increases in the minimum wage are unlikely to divert students from degree attainment.